Exercise for people with hip or knee osteoarthritis: a comparison of land-based and aquatic interventions - Ann E Rahmann (Open Access Journal of Sports Medicine, 2010)
Ann E RahmannDivision of Physiotherapy, School of Health and Rehabilitation Sciences, The University of Queensland, St Lucia, Queensland, AustraliaAbstract: Expert opinion considers the referral of people with osteoarthritis (OA) for physiotherapy to be a core component of managing the functional disability and pain of the disease. Clinical guidelines for the physiotherapy management of people with OA focus on three main areas: exercise, pain relief, and specific manual therapy techniques. Land-based group and individual physiotherapy exercise programs, as well as manual therapy, have demonstrated a distinct benefit in favor of physiotherapy intervention. Similarly, both general and specific aquatic physiotherapy exercise programs have shown positive outcomes for people with OA. This review will focus primarily on therapeutic exercise to improve strength and fitness and reduce pain in people with hip or knee OA. An overview of the principles of hydrodynamics relevant to aquatic exercise is also included to facilitate an understanding of effective aquatic exercise programs. The issue of compliance with exercise programs will also be discussed. Clinicians will, therefore, gain an understanding of the benefits of land-based and aquatic exercise for people with OA.Keywords: exercise, physical therapy, aquatic therapy, hip and knee osteoarthritis, strength, pain, aerobic exercise